Sex bias in prospective follow-up observational studies with drugs carried out in a southern region of Europe - Santomà, Àlex; Jambrina, Anna Maria; Perisé, Adela; Armelles, Mercè; Perisé, Lluisa; Pareja, Clara; Rams, Neus; Rabanal, Manel (Frontiers in Pharmacology, 2024)
Introduction: The impact of sex bias in medical research is a matter of significant relevance and importance especially in the modern age. Despite notable improvements in sex equity across various societal fields, disparities in sex representation persist within clinical and pharmacological research. The objective of this article is to investigate the sex bias within Prospective Follow-up Observational Studies with Drugs authorized by the Advisory Commission on Post-Authorization Studies with Medicines in Catalonia, a southern European region. Methods: A retrospective study that analyses data from final reports of Prospective Follow-up Observational Studies with Drugs authorized by the Advisory Commission on Post-Authorization Studies with Medicines in Catalonia from 2015 to 2021. Disease categories and specific diseases, obtained from the Global Data Exchange, were evaluated for sex bias, comparing female participation to female prevalence. Results: There were 106,399 participants, including 43,778 female participants (42.5%). A significant underrepresentation of females was observed across various disease categories. Notably, in 12 out of 19 categories (63.2%), a pronounced female underrepresentation (sex bias ≤ 0.05) was evident, particularly in the categories of HIV/AIDS and sexually transmitted infections (sex bias = -0.5659). Furthermore, 11 categories (57.9%) also demonstrated significant female underrepresentation, with the same notable categories, HIV/AIDS and sexually transmitted infections (sex bias = -0.4439). When examining specific diseases, significant female underrepresentation was observed in 13 out of 29 diseases (46.4%), especially in HIV (sex bias = -0.4781). The overall findings indicate that the degree of sex bias was notably less favorable for females in numerous disease categories and specific conditions. Conclusion: Our study has demonstrated a significant sex bias within observational studies, mirroring patterns observed in clinical trials. Importantly, our findings highlight a pervasive underrepresentation of women across various disease categories and specific conditions. Despite efforts to promote both sexes inclusivity, our results emphasize the persistent challenges in achieving balanced sex representation in study populations. Furthermore, the absence of categorization of diseases based on male and female prevalence poses a significant challenge in accessing pertinent data, particularly concerning the sex distribution of specific diseases.